2019
DOI: 10.3390/machines7010016
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Friction Behavior Characteristics by Coating with Solid Lubricants

Abstract: Increasing the lifetime of machine elements whose operation involves the development of friction processes and diminishing energy losses by friction can be achieved by using solid lubricants. In this regard, a method applied to improve the friction behavior of machine elements is electrostatic coating of the surfaces of interest with polyester layers that include particles of solid lubricants, such as molybdenum disulfide or graphite. Experimental research was conducted to highlight the influence of normal for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…It was concluded that the multilayer perceptron models were superior to the other neural network models and the regression model. In [5], a method applied with the aim to improve the friction behavior of machine elements is electrostatic coating of the surfaces of interest with polyester layers that include particles of solid lubricant. Grey analysis was employed to identify sets of…”
mentioning
confidence: 99%
“…It was concluded that the multilayer perceptron models were superior to the other neural network models and the regression model. In [5], a method applied with the aim to improve the friction behavior of machine elements is electrostatic coating of the surfaces of interest with polyester layers that include particles of solid lubricant. Grey analysis was employed to identify sets of…”
mentioning
confidence: 99%
“…It was concluded that the multilayer perceptron models were superior to the other neural network models and the regression model. In [5], a method applied with the aim to improve the friction behavior of machine elements is electrostatic coating of the surfaces of interest with polyester layers that include particles of solid lubricant. Grey analysis was employed to identify sets of input factors that would lead to the most convenient values of the lifetime and energy friction losses, when using polyester layers that incorporate molybdenum or graphite particles.…”
mentioning
confidence: 99%